Information Retrieving Through Sensors for Smart Parking - Ibrahim Mekawy; Bardia Khalilian (Computational Algorithms and Numerical Dimensions)
By using Internet of Things (IoT) we can make the things easier for our livelihood. The concept of smart parking in sensors is the combination of IoT. I.E By sending the status of the parking IoT through the internet, So that any person can see that which parking IoT is empty through the map and can easily park the vehicle. By using IoT the user can track the availability of the parking IoT through the web application to park the vehicle. In the existing systems the parking done manually and the user will probably had cases for looking for parking IoT for long time and there will be a chance for mismatching of parking IoT for the user. Smart parking provides parking efficiency and it reduces the time of searching for parking. The main concept of smart parking is to reduce searching for the parking IoT. Smart parking can optimize the traffic flows in the entire cities. The application uses IoT sensors just to receive the information about the parking IoT ’s.